Formação docente transdisciplinar: uma proposta curricular nos Cursos de Licenciatura em Música da UECE e da UFC de Fortaleza-CE - Lima, Hebe de Medeiros (2013)
The objective of this research was to analyze the process of capacitation of musical educators with the perspective of a transdisciplinary pedagogical approach, taking into account the curricular matrix of the courses of musical habilitation in the Federal and State Public Universities in Fortaleza. To these considerations we discus the work of authors that deal with transdisciplinary proposals in curricula, such as Morin (2000), Nicolescu (2000), Libâneo (2005), Moraes (2008), and Nascimento (2008). The methodologyis qualitative, based on multiple case studies, using the fundamentals of Bogdan and Biklen (1994), Gómes (1996), Stake (1998), André (2005), Peres e Santos (2005), Yin (2005), Beaud e Weber (2007) e Gil (2009).The data was collected from the Political Pedagogical Projects of the above mentioned Musical Courses, as well as from interviews with the teachers that worked in the development of these curricular matrixes. The results show some possibilities and applications of transdisciplinary proposals in curricula, and its implications in the formations of musical educators.